Visual reaction times in strabismic amblyopia: a case-control study - Nuzzi, G.; Riggio, L.; Rossi, S. (Acta Biomedica Atenei Parmensis, 2007)
Background: Visual reaction times (RT) have been used for the evaluation of the response to visual stimuli in amblyopic subjects in a case-control study. Materials and Methods: A Study Group, consisting in nine subjects with amblyopia and anomalous retinal correspondence, and a Control Group of nine normal subjects, were examined. In order to measure RT a test was carried out using a personal computer, for generating the visual stimuli on a special 14” monitor and for recording the response. A program was specifically created to record the dimensions of the stimuli and times of presentation in milliseconds. An electrographic tracing controlled the visual fixation. Visual stimuli of different dimensions were presented to the amblyopic eye, the dominant and non dominant eye, and in binocular vision, and RT were recorded. Results: In all cases RT represented a decreasing function of the stimulus dimension, with no statistical difference between the two groups (p=0,471). In both groups, RT values deriving from the greatest stimuli were rather inferior to those measured with smaller stimuli (p